Mineral-induced bubbling effect and biomineralization as strategies to create highly porous and bioactive scaffolds for dentin tissue engineering - de Melo, Camila Correa da Silva Braga; Cassiano, Fernanda Balestrero; Bronze-Uhle, Érika Soares; Stuani, Vitor de Toledo; Bordini, Ester Alves Ferreira; Gallinari, Marjorie de Oliveira [UNESP]; de Souza Costa, Carlos Alberto [UNESP]; Soares, Diana Gabriela (Wiley, 2022)
The objective of the study was to assess the biological and mechanical characteristics of chitosan-based scaffolds enriched by mineral phases and biomineralized in simulated body fluid (SBF) as a possible biomaterial for dentin regeneration. Thus, porous chitosan scaffolds were prepared by the mineral-induced bubbling-effect technique and subjected to biomineralization to create biomimetic scaffolds for dentin tissue engineering. Suspensions containing calcium hydroxide, nanohydroxyapatite, or β-tricalcium phosphate were added to the chitosan (CH) solution and subjected to gradual freezing and freeze-drying to obtain CH-Ca, CH-nHA, and CH-βTCP porous scaffolds, respectively, by the bubbling effect. Then, scaffolds were incubated in SBF for 5 days at 37°C, under constant stirring, to promote calcium-phosphate (Ca-P) biomineralization. Scanning electron microscopy revealed increased pore size and porosity degree on mineral-containing scaffolds, with CH-Ca and CH-nHA presenting as round, well-distributed, and with an interconnected pore network. Nevertheless, incubation in SBF disrupted the porous architecture, except for CH-CaSBF, leading to the deposition of Ca-P coverage, confirmed by Fourier Transform Infrared Spectroscopy analyses. All mineral-containing and SBF-treated formulations presented controlled degradation profiles and released calcium throughout 28 days. When human dental pulp cells (HDPCs) were seeded onto scaffold structures, the porous and interconnected architecture of CH-Ca, CH-nHA, and CH-CaSBF allowed cells to infiltrate and spread throughout the scaffold structure, whereas in other formulations cells were dispersed or agglomerated. It was possible to determine a positive effect on cell proliferation and odontogenic differentiation for mineral-containing formulations, intensely improved by biomineralization. A significant increase in mineralized matrix deposition (by 8.4 to 18.9 times) was observed for CH-CaSBF, CH-nHASBF, and CH-βTCPSBF in comparison with plain CH. The bioactive effect on odontoblastic marker expression (ALP activity and mineralized matrix) was also observed for HDPCs continuously cultivated with conditioned medium obtained from scaffolds. Therefore, biomineralization of chitosan scaffolds containing different mineral phases was responsible for increasing the capacity for mineralized matrix deposition by pulpal cells, with potential for use in dentin tissue engineering.
Keywords: bioization; chitosan; dentin; mineral; scaffold; vital pulp therapy